Effect of Water Hyacinth Root Extract and Liquid Smoke on the Growth of Soybean Plants in Saline Soil - Salsabella, Zhella; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2024)
Soybean production can be increased by optimizing salinity marginal land and using Plant Growth Regulators (PGR) gibberellins. Phosphate solubilizing bacteria, specifically Pseudomonas fluorescens, were applied to help mitigate the elevated salt content in saline soil. The study aimed to describe the effect of water hyacinth root extract, liquid smoke, and their interaction on soybean plant growth. The study used a two-factor Randomized Group Design with the concentration of water hyacinth root extract (0 ppm, 500 ppm, 1000 ppm) and liquid smoke (0%, 1%, 2%). Data analysis used two-way ANOVA and continued with Duncan’s test. The results showed that the interaction between the concentration of water hyacinth root extract and the concentracion of liquid smoke significantly affected the number of leaves, plant wet biomass, number of pods, and pod biomass. The concentration of 1000 ppm water hyacinth root extract and 1% the concentration of liquid smoke is the best combination for the number of leaves of 14.67 strands, plant wet biomass of 15.33 grams, the number of pods 13.00 pods, and soybean plant pod biomass of 8.00 grams.